(untitled) (Research, Society and Development, 2022)
Approximately 20% of the mineral coal ash (MCA) generated worldwide, during the combustion of this fossil fuel, has been used to produce Portland cement. Other applications include soil improvement, ceramic industry, catalysis, and an application with special interest for this work which is the synthesis of zeolites. A hospital effluent clarification system was developed using MCA as an adsorbent for substances responsible for the color of the effluent generated by the laundry. A perfect mix tank promotes intimate contact between MCA and the effluent. At the exit of the mixing tank, a pH sensor correlated the value of this variable with the concentration of MCA in the mixture inside the tank. The information about the pH of the mixture was then sent to a programmable logical controller (PLC), which regulated the motor speed of a screw conveyor, with the aid of a frequency inverter. A color removal efficiency of the order of 99.8% was achieved. The proposed clarification system can operate both in batch and continuous. In the first case, the ideal operating conditions can be set. The strategy for adjusting operating conditions is to obtain an adequate nominal capacity for the system by reducing or increasing the number of cyclones per battery or the number of cyclone batteries.